Efficacy of Thai Herbal Extract Oral Care Products in Promoting Antimicrobial Health Among Healthy Volunteers - Pimporn Thongmuang; Kanittada Thongkao; Robert Wyn Owen; Yuttana Sudjaroen (Wolters Kluwer Medknow Publications, 2024)
Background: Reducing the levels of oral microbials, including Streptococcus mutans, Candida albicans, and Lactobacilli sp., would provide the prevention of dental caries and oral illness. Aims: To assess the antimicrobial effectiveness against oral pathogens of oral care products that contain urginea maritima extract (UM) extract, including lozenges, mouth spray, and mouthwash. Methods: The skin irritation test was conducted on each product compared with controls in healthy participants (n = 10) by the 24-hour closed obstruction patch test. The elimination of oral pathogens in participants (n = 30) before and after product usage (as per the instruction) was assessed using a modified dip slide test. Result: The physical appearance and stability of oral care products were almost preferable. When added to oral care products for oral health maintenance, the cariogenic bacteria S. mutans, Candida species, and Lactobacilli species have been found to exhibit antimicrobial activity.